PENGARUH PERSEPSI HARGA, KEPERCAYAAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Jasa Loundry Power Klin) - Lusiana Wismaningrum, 12.05.51.0113 (Students Journal of Economic and Management, 2017)
The study of the factors that affect customer satisfaction laundry service (Power Klin case study on Semarang). The purpose of this research is to analyze the influence of trust, perception of price and quality of service to customer satisfaction car air conditioner laundry service (Power Klin case study on Semarang). A sample of 100 respondents, the sampling method used was simple random sampling, by providing an equal opportunity for each element or member of the population to choose as a sample. Methods of data analysis using linear regression. The test results showed that (1) there are significant positive and significant correlation between price perception to customer satisfaction, (2) there are significant positive and significant correlation between the trust of the customer satisfaction and (3) there are significant positive and significant correlation between the quality of service to customer satisfaction.Â Keywords: price perception, trust, quality of service and customer satisfaction